72 Increasing Radiotherapy Induced DNA Damage by Inhibiting Repair Proteins. (12th October 2021) - Atkinson, B; Wilson, J
Abstract: Introduction: Fanconi anaemia (FA) is a rare genetic disorder displaying higher incidences of head and neck squamous cell carcinoma (SCC). The surgical excision of these cancers is challenging and often supplemented with radiotherapy. One novel concept to improve survival rates is to increase the susceptibility of SCCs to radiotherapy. ATR is a protein responsible for homologous recombination repair (HRR) within the FA pathway and has been identified as a possible target for cancer therapy. Inhibition of ATR induces subsequent DNA damage. The primary objective of this study was to identify whether the inhibition of ATR can be achieved by exposing SCCs to mild hyperthermia. This novel concept aims to improve survival rates of patients with SCCs who require surgical excision and subsequent radiotherapy. Method: By using a HRR assay it was possible to examine levels of DNA repair in various SCC cell lines following the exposure to radiation. These were compared to cells treated with heat, an ATR inhibitor and a mixture of both to determine whether heat reduces HRR. Results: Repeated HRR assay's showed SCC's treated with heat, ATR inhibitor and a mixture of both before exposure to radiation underwent significantly lower levels of HRR compared to cells within the control. Conclusions: Reduced HRR following exposure to heat increases the susceptibility of SCCs to radiotherapy. It is hoped that in combination with the surgical excision, this study will help to improve the outcomes of patients with head and neck carcinomas by improving the efficacy of radiotherapy.